miR-150 downregulation contributes to the high-grade transformation of follicular lymphoma by upregulating FOXP1 levels - Musilova, Katerina; Devan, Jan; Cerna, Katerina; Seda, Vaclav; Pavlasova, Gabriela; Sharma, Sonali; Oppelt, Jan; Pytlik, Robert; Prochazka, Vit; Prouzova, Zuzana; Trbusek, Martin; Zlamalikova, Lenka; et al. (Blood, 2018)
Follicular lymphoma (FL) is a common indolent B-cell malignancy with a variable clinical course. An unfavorable event in its course is histological transformation to a high-grade lymphoma, typically diffuse large B-cell lymphoma. Recent studies show that genetic aberrations of MYC or its overexpression are associated with FL transformation (tFL). However, the precise molecular mechanisms underlying tFL are unclear. Here we performed the first profiling of expression of microRNAs (miRNAs) in paired samples of FL and tFL and identified 5 miRNAs as being differentially expressed. We focused on one of these miRNAs, namely miR-150, which was uniformly downmodulated in all examined tFLs (∼3.5-fold), and observed that high levels of MYC are responsible for repressing miR-150 in tFL by binding in its upstream region. This MYC-mediated repression of miR-150 in B cells is not dependent on LIN28A/B proteins, which influence the maturation of miR-150 precursor (pri-miR-150) in myeloid cells. We also demonstrated that low miR-150 levels in tFL lead to upregulation of its target, namely FOXP1 protein, which is a known positive regulator of cell survival, as well as B-cell receptor and NF-κB signaling in malignant B cells. We revealed that low levels of miR-150 and high levels of its target, FOXP1, are associated with shorter overall survival in FL and suggest that miR-150 could serve as a good biomarker measurable in formalin-fixed paraffin-embedded tissue. Overall, our study demonstrates the role of the MYC/miR-150/FOXP1 axis in malignant B cells as a determinant of FL aggressiveness and its high-grade transformation.
Keywords: difúzní velkobuněčný B-lymfom; Transcriptional Activation; Up-Regulation; protoonkogenní proteiny c-myc; upregulace; Prognosis; regulace genové exprese u nádorů; mikro RNA; represorové proteiny; down regulace; Proto-Oncogene Proteins c-myc; forkhead transkripční faktory; Lymphoma, Follicular; Repressor Proteins; Lymphoma, Large B-Cell, Diffuse; MicroRNAs; Down-Regulation; prognóza; Forkhead Transcription Factors; Humans; Gene Expression Regulation, Neoplastic; aktivace transkripce; nádorová transformace buněk; folikulární lymfom; Cell Transformation, Neoplastic; lidé